Concepts and Signs of Risk in Entrepreneurship - BODNAR, Tatyana V.; RІEZNIKOVA, Viktoriia V.; KRAVETS, Iryna M. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).06, 2020)
The article is devoted to the study of the concept and features of risks in entrepreneurship. The points of view of scientists concerning the concept of risks are analyzed, two main concepts of risk are outlined: classical and neoclassical. The focus is on several risk concepts in the context of the doctrine of objective liability for damages: integral risk theory, theory of spheres, risk-benefit theory. The article systemizes the existing approaches to the essence and content of such a phenomenon as a risk in entrepreneurship: (1) risk is interpreted as uncertainty, indeterminacy, attribute of decision-making in a situation of uncertainty; (2) the risk is defined as the probability of deviation of the actual result from the expected; (3) the risk arises as an activity; (4) the risk is treated as the threat (danger) of deviation of the results of specific decisions or actions from the expected; (5) risk is interpreted as a system (complex) of individual components and elements (integrated approach). Different points of view of researchers concerning the signs of entrepreneurial risks are considered, author's signs of risk in entrepreneurship are singled out. Two ways of further development of the economic legislation in the part of legal support of freedom of entrepreneurship, as well as risk inherent in it, business risk management, etc. are proposed.